2021
DOI: 10.1371/journal.pone.0251688
|View full text |Cite
|
Sign up to set email alerts
|

Is the HPV-test more cost-effective than cytology in cervical cancer screening? An economic analysis from a middle-income country

Abstract: Objective To report a modelling study using local health care costs and epidemiological inputs from a population-based program to access the cost-effectiveness of adopting hrHPV test. Methods A cost-effectiveness analysis based on a microsimulation dynamic Markov model. Data and costs were based on data from the local setting and literature review. The setting was Indaiatuba, Brazil, that has adopted the hrHPV test in place of cytology since 2017. After calibrating the model, one million women were simulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…The Roche Linear Array, as used in this study for HPV genotyping, is not yet an approved primary screening test in South Africa, despite studies reporting it fulfills the clinical accuracy requirements to detect cervical intraepithelial neoplasia of grade 2 or worse (CIN2 +) [24][25][26]. Given that evidence has shown that HPV-based screening provides 60-70% greater protection against invasive cervical carcinomas compared with cytology [27] and is more cost-effective in the long-term [28], additional research is needed to determine other practical implementation impacts of changing from cytology-to HPV-based primary screening for cervical cancer (i.e. ; financial, operational, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…The Roche Linear Array, as used in this study for HPV genotyping, is not yet an approved primary screening test in South Africa, despite studies reporting it fulfills the clinical accuracy requirements to detect cervical intraepithelial neoplasia of grade 2 or worse (CIN2 +) [24][25][26]. Given that evidence has shown that HPV-based screening provides 60-70% greater protection against invasive cervical carcinomas compared with cytology [27] and is more cost-effective in the long-term [28], additional research is needed to determine other practical implementation impacts of changing from cytology-to HPV-based primary screening for cervical cancer (i.e. ; financial, operational, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Another study predicting the cost-effectiveness of screening with hrHPV testing showed a decrease in the incremental cost-effectiveness ratio (ICER) of (USD −6.16) relative to conventional cervical cytology. Quality-adjusted life-years (QALYs) were 386.98 for cytology and 390.80 for hrHPV-based testing, respectively [ 58 , 59 ]. A combination of LBC and HPV testing methods is called co-testing.…”
Section: Review Resultsmentioning
confidence: 99%
“…Our results highlight the need to conduct an economic evaluation of alternatives to strength the cervical cancer screening program in Bogotá. For example, including HPV testing and self-sampling have shown positive impacts in Argentina, Brazil and Mexico [ 80 – 83 ].…”
Section: Discussionmentioning
confidence: 99%